Efektivitas Anggaran Sebagai Variabel Intervening: Analisis Faktor- Faktor yang Mempengaruhi Kinerja OPD - Syafrida Hani; M Firza Alpi (Jurnal Akuntansi dan Pajak, 2023)
The purpose of this study was to determine the effect of accountability on performance with budget effectiveness as an intervening variable in North Sumatra government OPD, to determine the effect of transparency on performance with budget effectiveness as an intervening variable in North Sumatra government OPD. This research is a quantitative study using data obtained from questionnaires and measured using a Likert scale. The source of data in this study is primary data. The data analysis used is validity test, reliability test, classical assumption test and path analysis. The hypothesis is tested by using the test. The results of this study indicate that: 1) There is a positive and significant effect of accountability on the performance of OPD, 2) There is a positive and significant effect of transparency on the performance of OPD, 3) There is a positive and significant effect of accountability on the effectiveness of the budget, 4) There is a significant influence on the effectiveness of the budget. positive and significant transparency on budget effectiveness, 5) There is a positive and significant effect of budget effectiveness on OPD performance, 6) There is a positive and significant effect of accountability on budget effectiveness with OPD performance, 7) There is a positive and significant effect of transparency on budget effectiveness with OPD performance